New antimycobacterial 2,3-dihydro-1-alkylindole-2-thiones - Waisser, K; Heinisch, L; Slosárek, M; Janota, J (Folia microbiologica, 2006)
A series of 2,3-dihydroindole-2-thiones was evaluated for in vitro antimycobacterial activity against Mycobacterium tuberculosis, M. kansasii, M. fortuitum, two strains of M. intracellulare and three strains of M. avium. 2,3-Dihydro-1-methyl-2-thioxoindole-3-one and 2,3-dihydro-1-butyl-2-thioxoindole-3-one were the most active substances against potentially pathogenic strains, being more active than isoniazide.
Keywords: Anti-Bacterial Agents; Antitubercular Agents; thioketony; Microbial Sensitivity Tests; mikrobiální testy citlivosti; Mycobacterium fortuitum; antibakteriální látky; Mycobacterium avium Complex; Nontuberculous Mycobacteria; antituberkulotika; netuberkulózní mykobakterie; Mycobacterium avium komplex; isoniazid; Indoles; Mycobacterium kansasii; Mycobacterium tuberculosis; Thiones; Isoniazid; indoly